Characterization of Patients with Diabetic Foot Ulcers Managed at Moi Teaching and Referral Hospital, Eldoret, Kenya - Sophie, Obare K.; Ayumba, Barry R.; Neford, Neford Ongaro (British Journal of Healthcare and Medical Research, 2026)
Background: A diabetic foot ulcer is any break in the epidermis below the ankle, in a person with diabetes mellitus. Among these patients, the lifetime prevalence of developing foot ulcers is 15%. Neuropathy and poor blood circulation create a suitable environment for occurrence of Diabetic Foot Ulcers (DFUs), gangrene and infection. These foot complications in individuals with diabetes mellitus are becoming a major public health problem in Africa and can be attributed to late presentation, poor awareness both among healthcare workers and patients, as well as late referral once they occur. Locally and at Moi Teaching and Referral Hospital (MTRH), there is paucity of publication on this subject, hence the need of this study. Objective: To describe the sociodemographic characteristics and the patterns of diabetic foot ulcers in patients manged at MTRH, Eldoret, Kenya. Methods: A cross sectional study done at MTRH, involved a census of 89 adult patients with diabetic foot ulcers, who met inclusion criteria. They comprised of those seen in the surgical wards and in the diabetic clinic. Data was collected using interviewer administered questionnaires. The Researcher documented crucial information from the history and physical examination. The variables studied were coded and assigned numerical values for quantitative analysis. Data was summarized as mean ± SD and presented using tables, pie charts and graphs. Results: The mean age was 55.3(SD±12.2) years. Female were 37(42%) and males were 52(58%). Formally educated were 80(90%), while 9(10%) had none. Cigarettes smokers were 22 (25%) while 40 (45%) took alcohol. Their Body Mass Index (BMI) values showed that 7(8%) were underweight, 55(62%) were of normal weight, 22(24%) were overweight and 5(6%) were obese. Glycated haemoglobin (HBA1C) was normal in 40 (45%) and abnormal in 49(55%) patients. Features in association with peripheral neuropathy were: oedema (57%), numbness and pricking sensation (both at 48%), fissures (47%), weakness (42%), dryness (39%), burning sensation (37%) and Tinea pedis (8%). Majority (90%) of the patients received appropriate footwear education, and 88.8% received education on self-examination. Comorbidity included: hypertension- 61%, retinopathy- 36% and nephropathy- 27%. The distribution of DFUs based on Wagner classification: Grades 1- 4 were 21.3%, 33.7%, 31.5%, and 13.5% respectively. DFUs were found to be significantly associated with hypertension (p<0.001) and retinopathy (p<0.001). Conclusion: Majority of the patients were male. Many had abnormal HBA1C, while all had at least two or more features of peripheral neuropathy. Grade 2 ulcers and hypertension as comorbidity were the most common. Recommendations: Prevention of DFUs through early identification and correction of risk factors like high BMI, high HBA1C, peripheral neuropathy, smoking cigarettes and alcohol intake should be intensified.